The Effects of Mycovirus BmPV36 on the Cell Structure and Transcription of Bipolaris maydis - Yajiao Wang; Qiusheng Li; Yuxing Wu; Sen Han; Ying Xiao; Lingxiao Kong (Journal of Fungi, 2024)
Bipolaris maydis partitivirus 36 (BmPV36) is a mycovirus that can significantly reduce the virulence of the host Bipolaris maydis, but its hypovirulence mechanism is not clear. To investigate the response of B. maydis to BmPV36, the effects of BmPV36 on host cell structure and gene expression were studied via transmission electron microscopy and transcriptome sequencing using BmPV36-carrying and virus-free mycelium on the second and fifth culture. The results of transmission electron microscopy showed that the cell wall microfibrils of B. maydis were shortened, the cell membrane was broken, and membrane-bound vesicles and vacuoles appeared in the cells after carrying BmPV36. Transcriptome sequencing results showed that after carrying BmPV36, B. maydis membrane-related genes were significantly up-regulated, but membrane transport-related genes were significantly down-regulated. Genes related to carbohydrate macromolecule polysaccharide metabolic and catabolic processes were significantly down-regulated, as were genes related to the synthesis of toxins and cell wall degrading enzymes. Therefore, we speculated that BmPV36 reduces the virulence of B. maydis by destroying the host’s cell structure, inhibiting the synthesis of toxins and cell wall degrading enzymes, and reducing cell metabolism. Gaining insights into the hypovirulence mechanism of mycoviruses will provide environmentally friendly strategies for the control of fungal diseases.